Experiences and career intentions of combat-deployed UK military personnel. (26th February 2018) - Morris-Butler, R; Jones, N; Greenberg, N; Campion, B; Wessely, S
Abstract: Background: Most studies of the psychological impact of military deployment focus on the negative and traumatic aspects. Less is known about the full range of deployment experiences nor how these may impact on career intentions. Aims: To examine subjective operational experiences and career intentions in deployed UK military personnel using data gathered toward the end of an operational deployment. Methods: Data were gathered during deployment in Iraq and Afghanistan. A self-report survey collected data on sociodemographic, operational and military factors. Respondents provided their strength of agreement or disagreement with six potentially positive deployment experiences and their endorsement or rejection of six possible career intentions. Two mental health measures assessed symptoms of common mental disorder and post-traumatic stress disorder. Results: Responses were 681 in Iran 2009 (100% response rate); 1421 in Afghanistan in 2010 (100%), 1362 in 2011 (96%) and 860 in 2015 (91%). Five of the potentially positive outcomes were endorsed by >50% of the sample: confidence about remaining healthy after returning home, pride in accomplishments, increased confidence in abilities, improved unit cohesion and experiencing a positive life effect. Ninety per cent of respondents planned to continue in service after returning home. Fewer positive deployment experiences, poorer mental health, lesser unit cohesion and more negative impressions of leadership were significantly associated with intention to leave service. Conclusions: Contrary to the popular belief that UK military personnel deployed to Iraq or Afghanistan experience negative outcomes, this paper shows that deployment can be a positive experience for a substantial majority of deployed personnel.